The Okanagan Charter to improve wellbeing in higher education: shifting the paradigm - Ginter, Peter M.; Kennedy, Rebecca; Erwin, Paul C.; Reed, Wendy (Frontiers in Education, 2024)
There is a growing trend among US universities and colleges to become Health Promoting Universities (HPUs) and adopt the Okanagan Charter. This trend is based on the aspirations of these universities and colleges to infuse health into everyday operations and improve the wellbeing of people, places and the planet. As university and colleges adopt the Okanagan Charter there is little guidance on how to think about wellbeing and address the social and planet determinants of health on a university campus. In addition, there is a need to understand the strategies of HPUs and how they differ compared to current activities of schools or programs of public health and medical centers already focused on improving health and wellness. HPUs will be a driving force for campus public health and improvements in wellbeing as additional higher education institutions move in this direction.